Strategy to prevent cardiac toxicity induced by polyacrylic acid decorated iron MRI contrast agent and investigation of its mechanism. (November 2019) - Fu, Hao; Miao, Chongchong; Rui, Yuanpeng; Hu, Fenglin; Shen, Ming; Xu, Hong; Zhang, Chunfu; Dong, Yi; Wang, Wenping; Gu, Hongchen; Duan, Yourong
Abstract: Polyelectrolyte modified iron oxide nanoparticles have great potential applications for clinical magnetic resonance imaging (MRI) and anemia treatments, however, possible associated heart toxicity is rarely reported. Here, polyacrylic acid (PAA)-coated Fe3 O4 nanoparticles (PION) were synthesized and lethal reactions appeared when it was applied in vivo . The investigation of underlying mechanism showed that PION could break electrolyte balance and further resulted in serious heart failure, which was observed under color doppler ultrasound and dynamic vector blood flow technique. The results demonstrated that PION had a strong absorption tendency for divalent ions and the maximum tolerated dose (MTD) was lower than 100 mg/kg. From electrocardiography (ECG), PION presented an obvious impact on CaV1.2 ion channel, which leading to fatal arrhythmia. An appropriate solution for preventing this deadly effect was pre-chelation Ca 2+ (n(Ca ) : n(COOH)  = 3: 8) to PION (PION-Ca), which displayed much higher cardiac and electrophysiological safety when sealing the binding point of divalent cation ions with PAA. The injection in Beagle dogs further confirmed the safety of PION-Ca. This study explored the mechanism and offered a solution for cardiac toxicity induced by PAA-coated nanoparticles, which guides for enhancing the safety of such polyelectrolyte decorated nanoparticles and provides assurance for clinical applications.